Coastwide Otolith Signatures of Juvenile Atlantic Menhaden, 2009–2011. Issue 1 (21st December 2014) - Anstead, Kristen A.; Schaffler, Jason J.; Jones, Cynthia M.
Abstract: The Atlantic Menhaden Brevoortia tyrannus is a clupeid that plays a critical role in the marine food web and supports one of the largest fisheries on the U.S. East Coast. Along with a decrease in overall numbers and spawning stock biomass, recruitment levels have remained low since the 1990s. Atlantic Menhaden use numerous estuaries along the Atlantic coast for juvenile development before recruiting to the adult population, but the contribution of each of these nursery grounds is currently unknown. Chesapeake Bay is thought to contribute 70% of the total recruits, although this estimate is over 20 years old and predates current low recruitment levels. We investigated the potential of trace element (Li, Mg, Mn, Rb, Sr, Y, Ba, and Pb) and stable isotope ratio (δ 13 C and δ 18 O) signatures in otoliths to distinguish among Atlantic Menhaden collected from various nursery grounds along the U.S. Atlantic coast (Connecticut to South Carolina) during 2009–2011. Juveniles were classified to four regional nursery areas with nearly 90% accuracy. Due to significant interannual variation in the chemical signatures, our attempts to classify juveniles from adjacent year‐classes or combined year‐classes resulted in lower accuracy. However, this study provides a 3‐year library of geochemical fingerprints for assigning adults to their regions of origin. This research builds the foundation for a comprehensive estimate of Atlantic Menhaden recruitment rates from each of the major nursery areas along the U.S. Atlantic coast for 2009–2011. Received May 28, 2014; accepted September 16, 2014